The effectiveness of preventive nursing care in Pneumonia associated with mechanical ventilation (Research, Society and Development, 2021)
Objective: to describe the effectiveness of nursing care based on scientific evidence, currently available in the literature for the prevention of pneumonia associated with mechanical ventilation in patients in the Intensive Care Unit. Method: integrative literature review, using the three MEDILINE, LILACS and BDENF databases, including the keywords prevention and pneumonia associated with mechanical ventilation, nursing care and pneumonia associated with mechanical ventilation and nursing care and prevention” Result: Included 15 studies, found 7 nursing care that contribute to the prevention of pneumonia associated with mechanical ventilation. The professionals' adherence to care for the prevention of pneumonia associated with mechanical ventilation must be recognized, in their daily lives, as effective actions in the work process, having in permanent education, the foundation to guarantee the effectiveness of care. As it is an effective change, the education and training of health professionals are key factors to increase adherence to the guidelines. In this context, monitoring the multidisciplinary team's feedback on measures to prevent VAP can be a strategy that points out gaps and health indicators to subsidize investments in improving health care practices, based on training and continuing education. Therefore, in this review, scientific evidence was identified that describes the effectiveness of nursing care in preventing VAP, thus guaranteeing our autonomy in care management.